2021
DOI: 10.1002/smtd.202100071
|View full text |Cite
|
Sign up to set email alerts
|

Cas9‐Cleavage Sequences in Size‐Reduced Plasmids Enhance Nonviral Genome Targeting of CARs in Primary Human T Cells

Abstract: T cell genome editing holds great promise to advance a range of immunotherapies but is encumbered by the dependence on difficult‐to‐produce and expensive viral vectors. Here, small double‐stranded plasmid DNA modified to mediate high‐efficiency homologous recombination is designed. The resulting chimeric antigen receptor (CAR)‐T cells display a similar phenotype, transcriptional profile, and in vivo potency to CAR‐T cells generated using adeno‐associated viral vector. This method should simplify and accelerate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…As a result of different optimization steps, in most publications on virus-free TCR/CAR knock-ins blunt-ended dsDNA or plasmids were used with the frequency of knock-in T cells reported in a range between 5-50% after 7-14 days of expansion (49,50,51,52,53). Based on experience of authors of this review, the number of recovered T cells 10 days after initiation of the editing procedure can reach 10-200 times the number of PBMCs used as input (51).…”
Section: Transgene "Knock-in" With Crispr-cas Gene Editingmentioning
confidence: 99%
“…As a result of different optimization steps, in most publications on virus-free TCR/CAR knock-ins blunt-ended dsDNA or plasmids were used with the frequency of knock-in T cells reported in a range between 5-50% after 7-14 days of expansion (49,50,51,52,53). Based on experience of authors of this review, the number of recovered T cells 10 days after initiation of the editing procedure can reach 10-200 times the number of PBMCs used as input (51).…”
Section: Transgene "Knock-in" With Crispr-cas Gene Editingmentioning
confidence: 99%
“…Modified guide RNAs (gRNAs) was synthesized by GeneScript. Guide RNAs were reconstituted at 1μg/μL in RNase free water, Cas9 proteins were produced by our lab as described in our previous work [32] , In brief, they were complexed in 2:1 gRNA to Cas9 molar ratio at room temperature for 20 min then electroporated into T cells immediately after complexing [32] .…”
Section: Methodsmentioning
confidence: 99%
“…Based on pAAV-TRAC-1928z plasmid (as described in our previous work [32] , named it as CD19-WT) we designed and cloned the pAAV-TRAC-1928z-1XX (named as CD19-1XX). Briefly, the CD19 CAR comprises a single chain variable fragment [19] scFv specific for the human CD19 (AXL CAR comprises a single chain variable fragment of anti-AXL [33] specific binding to human AXL), preceded by a CD8a leader peptide and followed by CD28 hinge, transmembrane and intracellular regions and CD3ζ intracellular domain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in insertions and deletions without a decrease in level of activity demonstrates how these modifications improve the nuclease’s editing efficiency. Jing et al (2021) included the same MS modification to their sgRNA and observed a 15% higher knock-in efficiency compared to unmodified sgRNA when attempting to knock-in predetermined template plasmids into primary human T cells. Ryan et al (2022) similarly engineered the MS and MP nucleotide modifications to their synthesized sgRNA structures and observed increased indel editing for the HBB gene within human primary T cells.…”
Section: Gene Editing Cargomentioning
confidence: 99%